The invention of the self : personal identity in the age of art - Spira, Andrew (London, UK ; Bloomsbury Academic, 2020)
"This book is an examination of personal identity, exploring both who we think we are, and how we construct the sense of ourselves through art. It proposes that the notion of personal identity is a psycho-social construction that has evolved over many centuries. While this idea has been widely discussed in recent years, Andrew Spira approaches it from a completely new point of view. Rather than relying on the thinking subject's attempts to identify itself consciously and verbally, it focuses on the traces that the self-sense has unconsciously left in the fabric of its environment in the form of non-verbal cultural conventions. Covering a millennium of western European cultural history, it amounts to an 'anthropology of personal identity in the West'. Following a broadly chronological path, Spira traces the self-sense from its emergence from the collectivity of the medieval Church to its consummation in the individualistic concept of artistic genius in the nineteenth century. In doing so, it aims to bridge a gap that exists between cultural history and philosophy. Regarding cultural history (especially art history), it elicits significances from its material that have been thoroughly overlooked. Regarding philosophy, it highlights the crucial role that material culture plays in the formation of philosophical ideas. It argues that the sense of personal self is as much revealed by cultural conventions - and as a cultural convention - as it is observable to the mind as an object of philosophical enquiry."--
preface acknowledgements 1. The Concept of the Self -- 2. The Emergence of the Self: the Structure of the Medieval Church and Popular, Heretical and Visionary Dissensions from it -- 3. The Resurrection of theoretical Self: Imaginative Empathy with the Suffering and Death of Christ -- 4. The Localisation of the Self: the Origins of Perspective and the Accommodation of the Self in Pictorial Space -- 5. The Necessitation of the Self: the Ennoblement of the Artist and the Invention of an Archetype -- 6. The Abstraction of the Self: the Secularisation of Subject-Matter and the Commodification of Art -- 7. The Imaginary Environments of the Self: its Physical and Intellectual Frames of Mind -- 8. The Privatisation of the Self: Fireplaces, Beds and Mirrors -- 9. The Automation of the Self: the Material Culture of Time-keeping -- 10. The Sensibilities of the Self: Courtesy, Conversation, Letter-writing and Novel-reading -- 11. The Behaviour of the Self: the Codification of Sensibility in Domestic Life -- 12. -- The Portrayal of the Self: Facial Expression and the Language of Personal Emotion -- 13. The Enjoyment of the Self: Sexuality and the Valorisation of Meaningless Pleasure -- 14. The Embodiment of the Self: the Awakening to Sensation -- 15. The Autonomy of the Self: the Invention of Taste and Aesthetics -- 16. The Naturalness of the Self: the Picturesque Transformation of Nature into a Mirror of Personal Sublimity -- 17. The Consummation of the Self: the Sanctification of Art -- 18. The Seamless Garment of the Self -- bibliography index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on online resource; title from digital title page (viewed on September 11, 2020).
Keywords: Self (Philosophy); Self; Identity (Philosophical concept); Arts; Social & political philosophy; Electronic books